Hubungan Konflik Interpersonal Perawat dengan Tingkat Kepuasan Kerja di RS X Depok Tahun 2025 - Tila Januartiwi; Solehudin Solehudin; Inas Syabanasyah (Vitamin : Jurnal ilmu Kesehatan Umum, 2026)
This study aimed to analyze the relationship between nurses’ interpersonal conflict and job satisfaction at Hospital X Depok in 2025. Interpersonal conflict in the workplace may negatively affect nurses’ psychological well-being, performance, and quality of healthcare services, thereby reducing job satisfaction. This research employed a correlational analytic design with a cross-sectional approach. The study population consisted of all nurses working at Hospital X Depok, totaling 151 individuals, with a final sample of 121 respondents selected using purposive sampling. Data were collected using three instruments: a demographic questionnaire, an interpersonal conflict questionnaire based on Wexley’s theory, and the Minnesota Satisfaction Questionnaire (MSQ) short form to measure job satisfaction. Data analysis was conducted using univariate statistics and the Chi-Square test with a significance level of 0.05. The results showed that 55.4% of respondents experienced low interpersonal conflict, while 44.6% experienced high interpersonal conflict. Job satisfaction levels were relatively balanced, with 50.4% of nurses reporting high satisfaction and 49.6% reporting low satisfaction. The Chi-Square test indicated a significant relationship between interpersonal conflict and job satisfaction (p = 0.000). Nurses experiencing low interpersonal conflict tended to have higher job satisfaction, whereas those experiencing high interpersonal conflict predominantly reported low satisfaction. These findings highlight the importance of effective conflict management strategies, supportive leadership, and strengthened interpersonal communication to enhance nurses’ job satisfaction and improve the quality of healthcare services.